Tantangan Reformasi Birokrasi di Tengah Arus Demokratisasi: Tinjauan Kritis Berdasarkan Konsep Hisbah (Pengawasan) dalam Islam - Ahmad Yamin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
Democratization is a crucial political process that has shaped the development of the Indonesian government system since the collapse of the authoritarian regime. Within the framework of political development, the success of democratization is largely determined by the capacity of state institutions, particularly the bureaucracy, to translate democratic values into governance practices and public services. This article aims to analyze the relationship between democratization and bureaucratic reform, assess the extent to which bureaucratic capacity supports substantive and sustainable democracy, identify structural, cultural, and political challenges in bureaucratic reform, and examine its implications for governance, public accountability, and the quality of state services according to Islamic oversight. This research uses a qualitative method with a library research approach through analysis of books, scientific journal articles, policy documents, and reports from relevant national and international institutions. The results of the study indicate that democratization and bureaucratic reform in Indonesia are still progressing partially. Bureaucratic reform tends to be administrative and technocratic in nature, thus not fully strengthening the state's institutional capacity and is often hampered by the politicization of the bureaucracy and a less-than-democratic work culture. These findings confirm that strengthening a professional, neutral, and service-oriented bureaucracy is a key prerequisite for the realization of substantive and sustainable democracy within the framework of political development. Implementing Hisbah values through strengthening bureaucratic morality and public transparency has proven to be an effective antithesis to bureaucratic pathologies, while accelerating the achievement of clean and democratic governance. This study provides a theoretical contribution by integrating the Hisbah concept into the discourse of modern bureaucratic reform, offering a hybrid oversight model that combines formal audit mechanisms with the strengthening of transcendental integrity, which has been neglected in secular public administration studies.